Endophytic microbial diversity associated with commercial cultivar and crop wild relative banana variety could provide clues for microbial community management (2024)
Endophytes, microorganisms inhabiting internal plant tissues, play a pivotal role in plant growth and disease resistance. Moreover, previous studies have established that Musa plants derive disease protective functions from their microbiome. Notably, one of the crop wild relatives of banana, the Calcutta 4 variety, exhibits resistance to various phytopathogens such as Pseudocercospora fijiensis (P. fijiensis), while the Williams commercial cultivar (cv.) is highly susceptible. Therefore, this study aims primarily to characterize and compare the endophytic microbiota composition of Calcutta 4 and Williams banana plants when grown sympatrically. Alongside, differences in endophytic microbiome between plant sections (shoot or roots), growth phases (in vitro or greenhouse) and fitness factors such as the addition of plant growth-promoting bacteria Bacillus subtilis EA-CB0575 (T2 treatment) or infection by P. fijiensis (T3 treatment) were examined. Both culture-dependent and -independent techniques were used to evaluate these differences and assess the culturability of banana endophytes under varying conditions. Microbial cultures resulted in 331 isolates distributed across 54 genera when all treatments were evaluated, whereas 16 S sequencing produced 9510 ASVs assigned in 1456 genera. Alpha and beta diversity exhibited significant differences based on plant section, with an increase in phylogenetic diversity observed in plants with pathogen infection (T3) compared to control plants (T1). Additionally, four differentially abundant genera associated with nitrogen metabolism were identified in T3 plants and seven genera showed differential abundance when comparing varieties. When culture-dependent and -independent methods were compared, it was found that isolates represented 3.7 % of the genera detected by culture-independent methods, accounting for 12–41 % of the total data depending on the treatment. These results are crucial for proposing management strategies derived from crop wild relatives to enhance the resilience of susceptible commercial varieties against fitness factors affecting crop development. Additionally, they help to decipher the pathogenic effects of P. fijiensis in banana plants and advance the understanding of how plant domestication influences the endosphere.